Poly(ethylene glycol)-b-poly(lysine) copolymer bearing nitroaromatics for hypoxia-sensitive drug delivery. (1st January 2016) - Thambi, Thavasyappan; Son, Soyoung; Lee, Doo Sung; Park, Jae Hyung
Graphical abstract: Abstract: Hypoxia occurs in a variety of pathological conditions including stroke, rheumatoid arthritis, atherosclerosis, and tumors. In this study, an amphiphilic block copolymer, composed of poly(ethylene glycol) as the hydrophilic block and poly(ε-(4-nitro)benzyloxycarbonyl-l -lysine) as the hydrophobic block, was prepared for hypoxia-sensitive drug delivery. Owing to its amphiphilic nature, the block copolymer formed micelles and encapsulated doxorubicin (DOX) in an aqueous condition. The DOX-loaded micelles exhibited rapid intracellular release of DOX under the hypoxic condition, implying high potential as a drug carrier for cancer therapy. Statement of significance: Hypoxia occurs in a variety of pathological conditions including stroke, rheumatoid arthritis, atherosclerosis, and tumors. In this study, we developed a novel type of hypoxia-sensitive polymeric micelles (HS-PMs) that can specifically release the drug under the hypoxic conditions. HS-PMs were prepared using poly(ethylene glycol) as the hydrophilic block and poly(ε-(4-nitro)benzyloxycarbonyl-l -lysine) as the hydrophobic block. Owing to its amphiphilic nature, the block copolymer formed micelles and encapsulated doxorubicin (DOX) in an aqueous condition. The DOX-loaded micelles exhibited rapid intracellular release of DOX under the hypoxic condition. Overall, it is evident that the HS-PMs prepared in this study have the potential to effectively deliver hydrophobic drugs into the hypoxic cells involved in various intractable diseases.